ANALISIS PENGARUH CAPITAL ADEQUACY RATIO, LOAN TO DEPOSIT RATIO, NON PERFORMING LOAN DAN RETURN ON ASSET TERHADAP PENYALURAN KREDIT UMKM PADA BANK UMUM YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ade Efriany; Dewi Rahmayanti (Universitas Teuku Umar, 2016)
This research aims to obtain evidence about the effect of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Non Performing Loan (NPL), and Return of Assets (ROA) to MSMEs credit distribution of commercial banking which listed in the indonesia stock exchange period 2012- 2014. The population comprised 41 banking companies which listed in the Indonesia Stock Exchange in the period 2014. The sampel was selected is using the purposive sampling technique and it consisted of 11 banking companies. The data analysis technique was multiple regression analysis. Tests have been performed in this study gives the result of that capital adequacy ratio is not significant and positive effect. The opposite, loan to deposit ratio is significant and negative effect to total of MSMEs credit distribution. Meanwhile, non performing loan and return on asset were not significant and negative effect to total of MSMEs credit distribution.